The Positive Influence of Inquiry-Based Learning Teacher Professional Learning and Industry Partnerships on Student Engagement With STEM - Attard, Catherine; Berger, Nathan; Mackenzie, Erin (Frontiers in Education, 2021)
School teachers in science, technology, engineering and mathematics (STEM) face challenges in developing and maintaining high levels of student engagement and achievement in those disciplines. Consequently, declining numbers of students are electing these subjects beyond the compulsory years of schooling. A major factor in student engagement often is curriculum content being relevant to the lives of students outside the classroom. Two key ways teachers can enhance the real-world relevance of their lessons are inquiry-based learning and localizing the curriculum to provide an authentic context for teaching and learning. In this paper, we report a qualitative multiple case study into the perceived influences of inquiry-based learning on student engagement, as facilitated through teacher professional learning in the context of two major infrastructure programs in Sydney, Australia. Semi-structured interviews and focus groups were conducted with primary and secondary teachers who participated in professional learning about inquiry-based pedagogies, as well as with their students who undertook inquiry-based learning projects based on the infrastructure programs in their local community. Inductive and deductive content analyses using Attard’s Framework for Engagement with STEM illustrated how the combination of teacher professional learning, student inquiry-based learning, and localised industry-school partnerships enhanced student engagement across operative, cognitive, and affective domains. Another significant finding was the extent to which professional learning as the vehicle for inquiry-based learning and industry connections enhanced teachers’ pedagogical relationships and pedagogical repertoires in ways not possible with more conventional approaches to industry-school partnerships.